Treatment of neuromyelitis optica: an evidence based review - Douglas Sato; Dagoberto Callegaro; Marco Aurélio Lana-Peixoto; Kazuo Fujihara (Arquivos de Neuro-Psiquiatria)
Neuromyelitis optica (NMO) is an inflammatory disease of the central nervous system characterized by severe optic neuritis and transverse myelitis, usually with a relapsing course. Aquaporin-4 antibody is positive in a high percentage of NMO patients and it is directed against this water channel richly expressed on foot processes of astrocytes. Due to the severity of NMO attacks and the high risk for disability, treatment should be instituted as soon as the diagnosis is confirmed. There is increasing evidence that NMO patients respond differently from patients with multiple sclerosis (MS), and, therefore, treatments for MS may not be suitable for NMO. Acute NMO attacks usually are treated with high dose intravenous corticosteroid pulse and plasmapheresis. Maintenance therapy is also required to avoid further attacks and it is based on low-dose oral corticosteroids and non-specific immunosuppressant drugs, like azathioprine and mycophenolate mofetil. New therapy strategies using monoclonal antibodies like rituximab have been tested in NMO, with positive results in open label studies. However, there is no controlled randomized trial to confirm the safety and efficacy for the drugs currently used in NMO.